The power of a single number : a political history of GDP - Lepenies, Philipp, 1971- (Columbia University Press, 2016)
Since it was first widely used in the mid-twentieth century, GDP has become the most powerful statistical indicator of our time. Practically all governments adhere to the idea that GDP growth is a primary political target. And while criticism of this hegemonic measure has grown over the past decade, neither its champions nor its detractors deny its central importance in our political culture. In The Power of a Single Number, Philipp Lepenies tells the lively, unpredictable history of GDP's political acceptance-and eventual dominance. From Renaissance England to 1960s America, Lepenies tracks the emergence of GDP and its precursors, focusing on the individuals central to this development. He considers William Petty's failed attempt to popularize national income measures in the seventeenth century and then looks at the statistical work of Colin Clark in the early 1900s. An ingenious lone wolf, Clark remained something of an outsider in the economic community, but his ideas were extended by John Maynard Keynes and advanced a more focused study of national income. This work was furthered by Simon Kuznets, who emphasized GDP's ties to social well-being and set the stage for its future ascent. GDP finally achieved its singular status during World War II, assuming the importance it retains today. Lepenies's absorbing account helps us see this common measure anew and contextualizes current debates over the wisdom of the number's monolithic rule.